Study on the Microscopic Fracture Process and Acoustic Emission of Shale Based on Digital Image. (18th January 2021) - Tang, Motian; Wu, Zhonghu; Wang, Anli; Zuo, Yujun; Lou, Yili; Liu, Hao; Sun, Wenjibin
Abstract : The Niutitang Formation shale is often filled with calcite minerals, which significantly affects the physical and mechanical properties of shale reservoirs. To correctly understand the microscale fracture characteristics of the Niutitang Formation shale and the evolution of acoustic emission signals, this paper uses digital image processing technology to characterize the geometric characteristics and nonuniform distribution of calcite minerals in the shale at the microscale and then maps it to finite elements; uniaxial compression tests of different calcite vein inclination angles are carried out on a microscale. The results show that under the microscale structure, the changes in compressive strength and brittleness index of the Niutitang Formation shale with different calcite vein dip angles are all N-shaped. The calcite veins affect the distribution of the stress field, leading to significant differences in the shale fracture process and fracture mode. The shale fracture process can be divided into two types. The first type (0°, 15°, 30°, 45°) is that the shale matrix is destroyed first, and then, the calcite veins are destroyed; the second type (60°, 75°, 90°) is that the calcite veins are destroyed first, and then, the shale matrix is destroyed. Shale fracture modes can be divided into w-type, v-type, inverted v-type, and inverted z-type. The inclination angle of calcite veins has a significant influence on the AE evolution characteristics of the Niutitang Formation shale. According to the characteristics of the AE active period, it can be divided into two types: surge type and step type. The surge type has a short active period, the number of AE count surges is small, the AE peak is large, and the failure mode is relatively simple. The step type has a long active period, the number of AE count surges is large, and the AE peak is small, and the failure mode is relatively complicated. The research results provide important theoretical guidance for shale gas fracturing mining.